Legal controls for the validity of electronic signature - Avan Abdelaziz Reda (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
In the era of the technical revolution, all legal and administrative transactions are carried out electronically using modern technical devices, especially computer and internet. These transactions have encountered legal difficulties concerning proving them and specifying their contents. The traditional form of writing is not in electronic transactions. The written signature disappears to replace the electronic signature. Which requires the organization of legislation to recognize his pilgrimage, as electronic transactions need to be documented by the issuance of specialized bodies to investigate the integrity of electronic transactions in terms of content and content and validity of the issuance of those attributed to him A certificate of electronic certification has been issued attesting to the validity and validity of this signature and is to be relied upon in the execution of these electronic transactions. The electronic signature is a complex technical process. It is not necessary for the legal effects to be established and the legal authority to be obtained. The conditions stipulated in the Electronic Signature Law and the Evidence Law must be met. The electronic signature must meet the technical and technical conditions specified by the competent authorities. A statement of the electronic signature images and the position of the legislations thereof, and a statement of the competent authorities issuing the electronic certificates.